P15 A structural MRI study of motor conversion disorder: evidence of bilateral reduction in thalamic volume. Issue 10 (7th September 2012) - Nicholson, T; Aybek, S; Kempton, M; David, A; Kanaan, R
Abstract : Objective: Conversion disorder is the presence of neurological symptoms that are not due to neurological disease and are thought to be psychological in origin. It is assumed that patients have normal brain anatomy; structural brain abnormalities of potential aetiological relevance generally preclude the diagnosis. However, it remains possible there are subtle neuroanatomical differences that are only discernable at the group, rather than at the patient level. We aimed to test this hypothesis by comparing high-resolution MRI scans of patients with motor conversion disorder with healthy controls using a Region Of Interest (ROI) approach. Method: 15 patients with ICD-10 diagnoses of motor conversion disorder with symptom onset within 2 years and 31 age- and sex-matched healthy controls had high resolution Spoiled Gradient Recalled sequence scanning on a 3 T MRI scanner. ROIs, chosen on the basis of previous reports or on theoretical grounds, were placed on the bilateral amygdala, thalamus, caudate and lentiform nuclei. Freesurfer V.5.0 software was used to identify, label and measure the anatomical structure volumes. Results: There were uncorrected reductions in bilateral thalamic volume in patients compared to controls (left thalamus p=0.001, right thalamus p=0.002). Intracranial volume was also reduced in patients, however (p=0.012), and when corrected for this the thalamic reductions remained significant (left thalamus p=0.02, right thalamus p=0.05) and there was a significant (p=0.05) reduction in the volume of the left, but not the right, lentiform nucleus. There were no other ROI differences. Conclusion: We have found evidence for reduced volume of the thalamus in conversion disorder. These changes could be secondary to chronic limb immobility as there is some evidence of similar thalamic volume losses after limb amputation. Longitudinal studies of conversion disorder patients, particularly re-scanning post recovery, would be needed to address this question. If thalamic volume changes are found to correlate to level of limb disuse such changes would be a strong indicator of the severity of this disorder in terms of the amount of actual, as well as reported, immobility. However, a functional imaging study (Vuilleumier et al, 2001) has found evidence of reduced activation of the thalamus (and basal ganglia) in symptomatic conversion disorder patients and it therefore remains possible these changes could be of aetiological or mechanistic significance.